Parental Volunteering in Shaping the Character of Independent Learners in Primary Islamic Schools - Masruri, Muhammad; Ningsih, Tutuk; Kurniawan, Heru; Rahayu, Sri (Advances in Humanities and Contemporary Studies, 2024)
‘Merdeka Belajar’ emphasises cognitive outcomes and learners’ skills and character development. Volunteering is one dimension of parental involvement, representing their voluntary contributions towards the progress and achievement of the school’s objectives. This study aimed to understand and identify the relationship and role of parental volunteering in shaping the character of independent learners at MIN 22 Jakarta. The research method employed in this study was a combination of approaches utilising the sequential explanatory design model. The hypothesis posited a positive and significant relationship between parental volunteering and the character formation of independent learners at MIN 22 Jakarta. The research subjects encompassed parents and fifth-grade students at MIN 22 Jakarta, with data sources derived from questionnaires, documents, photographs, workbooks, and school journals. Two experts assessed Questionnaire validity through logical and empirical validation processes and utilising the corrected item-total correlation method with SPSS 24. Reliability was tested using Cronbach’s alpha calculation. The sampling technique utilised in this study was simple random sampling with a 5% sampling error. Quantitative data analysis was performed to ascertain the existence and direction of relationships among variables using the Pearson product-moment correlation test and a two-sided significance test (t-test) to determine the significance of the relationships. Qualitative data collection involved interviews, observations, and document analysis. Qualitative data analysis was conducted using the Miles and Huberman model, performed interactively through data collection, data reduction, data classification and presentation, and conclusion drawing and verification. The results of the correlation test yielded r-value > r-table, specifically 0.356 > 0.227, and the significance test resulted in t-value > t-table, precisely 3.317 > 1.665, confirming the acceptance of the research hypothesis; there was a positive and significant relationship between parental volunteering and the formation of character in independent learners. Based on the collected data, parental volunteering in education plays a significant role in shaping the character of commitment and independence.